2010
DOI: 10.1038/hdy.2009.193
|View full text |Cite
|
Sign up to set email alerts
|

Segregation distortion in chicken and the evolutionary consequences of female meiotic drive in birds

Abstract: As all four meiotic products give rise to sperm in males, female meiosis result in a single egg in most eukaryotes. Any genetic element with the potential to influence chromosome segregation, so that it is preferentially included in the egg, should therefore gain a transmission advantage; a process termed female meiotic drive. We are aware of two chromosomal components, centromeres and telomeres, which share the potential to influence chromosome movement during meioses and make the following predictions based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 39 publications
1
38
1
Order By: Relevance
“…Currently, our knowledge of the distribution of meiotic drivers and their fitness effects is very incomplete and is likely biased toward the overrepresentation of strong drivers with extreme fitness effects. However, there is mounting evidence supporting the existence of subtle transmission ratio distorters (e.g., Zöllner et al 2004;Reed et al 2005;Aparicio et al 2010;Axelsson et al 2010) (however, the mechanism of distortion in these cases is often unknown). Similarly, although there is ample evidence that the recombination rate, as well as the strength and direction of heterochiasmy, varies across species, few allelic variants that influence sex-specific recombination rates have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, our knowledge of the distribution of meiotic drivers and their fitness effects is very incomplete and is likely biased toward the overrepresentation of strong drivers with extreme fitness effects. However, there is mounting evidence supporting the existence of subtle transmission ratio distorters (e.g., Zöllner et al 2004;Reed et al 2005;Aparicio et al 2010;Axelsson et al 2010) (however, the mechanism of distortion in these cases is often unknown). Similarly, although there is ample evidence that the recombination rate, as well as the strength and direction of heterochiasmy, varies across species, few allelic variants that influence sex-specific recombination rates have been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Similar actions are suggested for other speciation genes 13 . There is evidence for segregation distortion in chicken chromosomes involving loci with centromeric or telomeric locations 28 . The genomic distribution of divergence peaks in flycatchers is compatible with an involvement of telomeres as well, as some chromosomes showed divergence signals in both ends.…”
Section: Research Lettermentioning
confidence: 99%
“…Genomic techniques are now opening new avenues for detecting drive. For example, a recent study in chickens using genome-wide approaches revealed previously undetected drive around the centromere and telomeres of chromosome 1 (55), as predicted by the centric drive model. Such genome-wide approaches are likely to uncover many more examples of drive in the near future.…”
Section: Types Of Sges and Their Consequencesmentioning
confidence: 99%